PENGEMBANGAN KOMPETENSI PROFESIONAL GURU BIOLOGI SMA MELALUI PENDEKATAN PELATIHAN PENDALAMAN MATERI - Jahidin Jahidin; Bahtiar Bahtiar (Universitas Sebelas Maret, 2014)
High school biology teacher in carrying out their duties as educators and teachers master the four competencies required minimum.One is professional competence.Training aims is enhance the development of Professional Competence (DPC) biology teacher, and determine the amount of contribution (effect size) of the DPC training material deepening biology teacher.The training material consists of basic competency breeding seed plants, the theory of the origin of life and the proof, the human digestive system, excretory system of human, photosynthesis, regulation of the human system, the human reproductive system, as well as the impact of biotechnology to society and the environment.The training method includes three phases of activity. The first step is presentation of material by the instructor, the second step is assignment and training study material, and finally step is presentation and discussion.The training lasts eight forces with a duration of five days or the equivalent of 55 hours per batch.Training participants totaled 248 high school biology teacher of 12 County Southeast Sulawesi.Professional competence measuring instruments using a multiple-choice test of 40 items was.Cognitive level of professional competence developed by Anderson and Krathwohl to measure knowledge shutter remember, understand, apply, analyze, evaluate, and create.Tests carried out before the implementation of the training (pree test) and after the implementation of the training (post-test).The results showed an increase of DPC: 0-5% is 13 participants, 6-10% is 19 participants, 11-15% are 24 participants, 16-20% are 78 participants, 21-25% are 51 participants, 26-30% are 52 participants, 31 - 35% are 36 participants, 36-40% are 23 participants, 41-45% are 4 participants, and 45-50% are 0 participants.The DPC mean is 19.89% with moderate category.The results of partial correlation analysis showed a positive and significant relationship between value Pree test with post-test with a correlation coefficient of r = 0:47;p <0.01. Keywords: professional competence, biology teacher, training approach, deepening materials